Antibacterial thermoplastic resin composite material and preparation method thereof
By adding thymol-titanium dioxide core-shell antibacterial agent to the thermoplastic resin, the problem of insufficient antibacterial properties of existing thermoplastic resins is solved, and the efficient antibacterial properties of thermoplastic resin composite materials are achieved, meeting the high antibacterial requirements of automotive interior parts.
Patent Information
- Application Number
- CN202310950735.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-14
AI Technical Summary
The antibacterial properties of existing thermoplastic resins are insufficient and cannot meet the requirements of automotive interior parts with antibacterial rate of more than 97%.
Thymol-titanium dioxide core-shell antibacterial agent is used, and by adding the antibacterial agent to the thermoplastic resin, a core-shell antibacterial agent with thymol as the core and titanium dioxide as the shell is formed, which significantly improves the antibacterial properties of the thermoplastic resin composite material.
It significantly improves the antibacterial properties of thermoplastic resin composites, so that they can reach or exceed 97% antibacterial rates, meeting the high antibacterial requirements of automotive interior parts.
Smart Images

Figure BDA0004368255900000061 
Figure BDA0004368255900000081 
Figure BDA0004368255900000101
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and in particular relates to a thermoplastic resin composite material with good antibacterial performance and a preparation method thereof. Background Art
[0002] Thermoplastic resin is a widely used polymer polyester resin, including: PE-polyethylene, PP-polypropylene, PVC-polyvinyl chloride, PS-polystyrene, PA-polyamide, POM-polyoxymethylene, PC-polycarbonate, polyphenylene ether, polysulfone, rubber, etc. Thermoplastic resin has the advantages of good fatigue resistance, good heat resistance and excellent dimensional stability. At present, the weight reduction and energy saving requirements of automobiles require thermoplastic resins to be used in automobile interiors such as seats, steering wheels, instrument panels, and door inner sides. However, since these interior parts are in direct contact with people, thermoplastic resins are required to have low odor and antibacterial properties. Because the high antibacterial properties of thermoplastic resins can effectively inhibit the growth and spread of bacteria and viruses, improve people's health and hygiene levels; at the same time, it also avoids the growth of bacteria and microorganisms to produce odors, stains, and damage to materials.
[0003] As people pay more attention to health and hygiene, consumers have higher and higher requirements for the interior environment of cars. Therefore, providing thermoplastic resins with high antibacterial properties as vehicle interior materials can meet consumers' needs for health and comfort and enhance product competitiveness. Currently, environmentally friendly antibacterial agents such as chitosan are mainly added to thermoplastic resins. Although it can improve the antibacterial properties of thermoplastic resins, it still cannot meet the requirement of more than 97% antibacterial rate for automotive interior parts.
[0004] In view of these shortcomings, the present invention innovatively synthesizes a novel antibacterial thermoplastic resin composite material, which has good antibacterial properties. This thermoplastic resin composite material has not been reported so far, which has very important practical significance for expanding the application field of thermoplastic resin composite materials. Summary of the invention
[0005] In view of this, the present invention innovatively synthesizes a thermoplastic resin composite material with good antibacterial performance, which has good antibacterial performance and solves the technical problem of limited antibacterial ability of thermoplastic resin in the prior art.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] An antibacterial thermoplastic resin composite material, which consists of the following components in parts by weight:
[0008] Thermoplastic resin 90-110 parts
[0009] 2-4 parts of antibacterial agent
[0010] Antioxidant 0.1-0.5 parts
[0011] The antibacterial agent is a thymol-titanium dioxide core-shell type antibacterial agent.
[0012] The preparation method of the thymol-titanium dioxide core-shell antibacterial agent comprises the following steps:
[0013] (1) adding titanium dioxide, thymol and a cross-linking agent into an acetone aqueous solution, stirring and reacting to obtain a titanium dioxide-thymol mixed solution A;
[0014] (2) The titanium dioxide-thymol mixed solution A is filtered to obtain a solid B, and the solid B is washed and vacuum dried in sequence, and then ground to obtain a core-shell antibacterial agent with thymol as a core and titanium dioxide as a shell.
[0015] Preferably, the mass ratio of titanium dioxide, thymol and cross-linking agent in step (1) is (30-40): (30-36): (0.2-0.4).
[0016] The cross-linking agent is tert-butyl peroxide, dicumyl peroxide or 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane.
[0017] Preferably, the stirring reaction in step (1) refers to stirring the reaction at 40-60° C. for 8-12 h;
[0018] The vacuum drying temperature in step (2) is 50-70° C. and the drying time is 8-12 h; the product is ground through a 500-mesh sieve.
[0019] The antioxidant is one or a mixture of tris(2,4-di-tert-butyl)phenyl phosphite (Irganox168 for short), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (Irganox1010 for short) and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene (Irganox1330 for short) produced by BASF.
[0020] The thermoplastic resin is one of polyethylene (PE), polypropylene (PP), polystyrene (PS), polybutylene terephthalate (PBT) and polyamide 6 (PA6).
[0021] The antibacterial high-performance thermoplastic resin composite material and the preparation method thereof include the following steps:
[0022] (1) Weigh 80-100 parts of a thermoplastic resin, 2-4 parts of an antibacterial agent, and 0.1-0.5 parts of an antioxidant, mix and stir to obtain a mixture;
[0023] (2) Extruding the mixed material obtained in step (1) from an extruder and granulating it to obtain a thermoplastic resin composite material.
[0024] The thermoplastic resin is one of polyethylene (PE), polypropylene (PP), polystyrene (PS), polybutylene terephthalate (PBT) and polyamide 6 (PA6).
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The present invention prepares a core-shell antibacterial agent with thymol as the core and titanium dioxide as the shell, which can well improve the antibacterial properties of thermoplastic resin composite materials because:
[0027] ①Since the electronic structure of nano-titanium dioxide is characterized by a full TiO2 valence band and an empty conduction band, in a water and air system, when the electron energy reaches or exceeds its band gap energy, the electrons can be excited from the valence band to the conduction band, and corresponding holes are generated in the valence band. Under the action of the electric field, the electrons and holes are separated and migrate to different positions on the particle surface. The generated superoxide anion free radicals react (oxidize) with most organic matter, and the holes oxidize OH and H2O adsorbed on the TiO2 surface into ·OH. ·OH has a strong oxidizing ability, attacks the unsaturated bonds of organic matter or extracts H atoms to generate new free radicals, stimulates chain reactions, and ultimately causes bacterial decomposition.
[0028] ② Thymol can inhibit the synthesis of bacterial peptidoglycan and damage the bacterial morphology. Thymol can also destroy or degrade the bacterial cell wall, destroy the cytoplasmic membrane, and destroy the cell membrane protein structure. It can also cause the bacterial cytoplasm to condense and weaken the bacterial proton motility.
[0029] ③ The core-shell antibacterial agent prepared by the present invention has the characteristics of both nano titanium dioxide and thymol, and can achieve a synergistic antibacterial effect. DETAILED DESCRIPTION
[0030] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0032] The raw materials used in the following examples are as follows:
[0033] PBT (model 2002U), Polyplastics, Japan;
[0034] PP (model Z30S), Maoming Petrochemical;
[0035] PE (model 5070), Panjin ethylene;
[0036] PA6 (model CM1017), Toray, Japan;
[0037] PS (model 350), Guoqiao, Taiwan, China;
[0038] Titanium dioxide, Suzhou Yanzhiduo New Materials Co., Ltd.;
[0039] Deionized water, Xiamen Aoquan Environmental Protection Technology Co., Ltd.;
[0040] Thymol, Maoming Xiongda Chemical Co., Ltd.;
[0041] Acetone, Shandong Changyao New Materials Co., Ltd.;
[0042] Tert-butyl peroxide, Shandong Mingyue Chemical Co., Ltd.;
[0043] Antioxidants (models Irganox168, Irganox1010, Irganox1330), BASF;
[0044] Chitosan, Shandong Qiansheng Chemical Co., Ltd.
[0045] Preparation Example 1
[0046] (1) 300 g of titanium dioxide, 600 g of acetone, 800 g of deionized water, 300 g of thymol, and 2 g of cross-linking agent tert-butyl peroxide were added to a reaction vessel, and stirred for reaction at 40° C. for 8 h to obtain a titanium dioxide-thymol mixed solution A;
[0047] (2) The mixed solution A was filtered to obtain solid B, which was washed, dried under vacuum at 50° C. for 8 h, and then ground through a 500-mesh sieve to obtain the core-shell antibacterial agent M1.
[0048] Example 1
[0049] (1) Weigh 90 parts of PP, 2 parts of antimicrobial agent M1, and 0.1 parts of Irganox 1010, mix and stir evenly to obtain a mixture;
[0050] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material P1.
[0051] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.
[0052] Comparative Example 1
[0053] (1) Weigh 90 parts of PP and 0.1 parts of Irganox 1010, mix and stir evenly to obtain a mixture;
[0054] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material D1.
[0055] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.
[0056] Comparative Example 2
[0057] (1) Weigh 90 parts of PP, 2 parts of commercial antibacterial agent chitosan, and 0.1 parts of Irganox 1010, mix and stir evenly to obtain a mixture;
[0058] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material D2.
[0059] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.
[0060] The PP composite materials prepared in the above Example 1 and Comparative Examples 1-2 were made into test strips using an injection molding machine. The test data are as follows:
[0061]
[0062] It can be seen from the above table that the antibacterial property of the composite material prepared in Example 1 is significantly better than that of Comparative Examples 1-2.
[0063] Preparation Example 2
[0064] (1) 400 g of titanium dioxide, 800 g of acetone, 1.0 kg of deionized water, 360 g of thymol, and 4 g of a cross-linking agent, tert-butyl peroxide, were added to a reaction vessel, and stirred at 60° C. for 12 h to obtain a titanium dioxide-thymol mixed solution A;
[0065] (2) The mixed solution A was filtered to obtain solid B, which was washed, vacuum dried at 70° C. for 12 h, and then ground through a 500-mesh sieve to obtain the core-shell antibacterial agent M2.
[0066] Example 2
[0067] (1) Weigh 110 parts of PBT, 4 parts of antibacterial agent M2, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330, mix and stir to obtain a mixture;
[0068] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material P2.
[0069] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.
[0070] Comparative Example 3
[0071] (1) Weigh 110 parts of PBT, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;
[0072] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material D3.
[0073] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.
[0074] Comparative Example 4
[0075] (1) Weigh 110 parts of PBT, 4 parts of commercial antibacterial agent chitosan, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330, mix and stir to obtain a mixture;
[0076] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material D4.
[0077] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.
[0078] The PBT composite materials prepared in the above Example 2 and Comparative Examples 3-4 were made into test strips by injection molding machine, and the test data are as follows:
[0079]
[0080] It can be seen from the above table that the antibacterial performance of Example 2 is better than that of Comparative Examples 3-4.
[0081] Preparation Example 3
[0082] (1) 350 g of titanium dioxide, 700 g of acetone, 900 g of deionized water, 330 g of thymol, and 3 g of a cross-linking agent, tert-butyl peroxide, were added to a reaction vessel, and stirred at 50° C. for 10 h to obtain a titanium dioxide-thymol mixed solution A;
[0083] (2) The mixed solution A was filtered to obtain solid B, which was washed, vacuum dried at 60° C. for 10 h, and then ground through a 500-mesh sieve to obtain the core-shell antibacterial agent M3.
[0084] Example 3
[0085] (1) Weigh 100 parts of PE, 3 parts of antibacterial agent M3, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1010, mix and stir to obtain a mixture;
[0086] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material P3.
[0087] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.
[0088] Comparative Example 5
[0089] (1) Weigh 100 parts of PE, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1010, mix and stir evenly to obtain a mixture;
[0090] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material D5.
[0091] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.
[0092] Comparative Example 6
[0093] (1) Weigh 100 parts of PE, 3 parts of commercially available antibacterial agent chitosan, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1010, mix and stir evenly to obtain a mixture;
[0094] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material P3.
[0095] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.
[0096] The PE composite materials prepared in the above Example 3 and Comparative Examples 5-6 were made into test strips by injection molding machine, and the test data are as follows:
[0097]
[0098] It can be seen from the above table that the antibacterial performance of Example 3 is better than that of Comparative Examples 5-6.
[0099] Preparation Example 8
[0100] (1) 325 g of titanium dioxide, 655 g of acetone, 905 g of deionized water, 345 g of thymol, and 3.5 g of a crosslinking agent, 2,5-dimethyl-2,5-di-tert-butyl peroxide, were added to a reaction vessel, and stirred at 45° C. for 11 h to obtain a titanium dioxide-thymol mixed solution A;
[0101] (2) The mixed solution A was filtered to obtain solid B, which was washed, vacuum dried at 65° C. for 11 h, and then ground through a 500-mesh sieve to obtain the core-shell antibacterial agent M4.
[0102] Example 4
[0103] (1) Weigh 95 parts of PA6, 4 parts of antibacterial agent M4, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1330, mix and stir to obtain a mixture;
[0104] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material P4.
[0105] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.
[0106] Comparative Example 7
[0107] (1) Weigh 95 parts of PA6, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;
[0108] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material D7.
[0109] The twin-screw extruder includes six temperature zones arranged in sequence. The temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, and the temperature of the sixth temperature zone is 260°C. The head temperature of the twin-screw extruder is 260°C and the screw speed is 320r / min.
[0110] Comparative Example 8
[0111] (1) Weigh 95 parts of PA6, 4 parts of commercial antibacterial agent chitosan, 0.1 parts of antioxidant Irganox1010, and 0.2 parts of antioxidant Irganox1330, mix and stir evenly to obtain a mixture;
[0112] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material P4.
[0113] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.
[0114] The PA6 composite materials prepared in the above Example 4 and Comparative Examples 7-8 were made into strips by injection molding machine for testing. The test data are shown in the following table:
[0115]
[0116] It can be seen from the above table that the antibacterial performance of Example 4 is better than that of Comparative Examples 7-8.
[0117] Preparation Example 5
[0118] (1) 315 g of titanium dioxide, 675 g of acetone, 925 g of deionized water, 335 g of thymol, and 3.5 g of crosslinking agent diisopropylbenzene peroxide were added to a reaction vessel, and stirred for reaction at 45° C. for 11 h to obtain a titanium dioxide-thymol mixed solution A;
[0119] (2) The mixed solution A was filtered to obtain solid B, which was washed, vacuum dried at 55° C. for 11 h, and then ground through a 500-mesh sieve to obtain the core-shell antibacterial agent M5.
[0120] Example 5
[0121] (1) Weigh 105 parts of PS, 3.5 parts of antibacterial agent N5, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, mix and stir to obtain a mixture;
[0122] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PS composite material P5.
[0123] The twin-screw extruder includes six temperature zones arranged in sequence, wherein the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 220°C, the temperature of the fourth temperature zone is 220°C, the temperature of the fifth temperature zone is 220°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 280r / min.
[0124] Comparative Example 9
[0125] (1) Weigh 105 parts of PS, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, mix and stir evenly to obtain a mixture;
[0126] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PS composite material D9.
[0127] The twin-screw extruder includes six temperature zones arranged in sequence, wherein the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 220°C, the temperature of the fourth temperature zone is 220°C, the temperature of the fifth temperature zone is 220°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 280r / min.
[0128] Comparative Example 10
[0129] (1) Weigh 105 parts of PS, 3.5 parts of commercial antibacterial agent chitosan, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, mix and stir to obtain a mixture;
[0130] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PS composite material D10.
[0131] The twin-screw extruder includes six temperature zones arranged in sequence, wherein the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 220°C, the temperature of the fourth temperature zone is 220°C, the temperature of the fifth temperature zone is 220°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 280r / min.
[0132] The PS composite materials prepared in the above Example 5 and Comparative Examples 9-10 were made into strips by injection molding and tested. The test data are shown in the following table:
[0133]
[0134] It can be seen from the above table that the antibacterial performance of Example 5 is better than that of Comparative Examples 9-10.
[0135] This shows that the thermoplastic resin composite material prepared by the method provided by the present invention has excellent antibacterial properties and can expand the application field of the thermoplastic resin composite material.
[0136] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0137] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. An antibacterial thermoplastic resin composite material, characterized in that: It is composed of the following components by weight: Thermoplastic resin 90-110 parts 2-4 parts of antibacterial agent Antioxidant 0.1-0.5 parts The antibacterial agent is a thymol-titanium dioxide core-shell type antibacterial agent.
2. The antibacterial thermoplastic resin composite material according to claim 1, characterized in that: The thermoplastic resin is one of polyethylene, polypropylene, polystyrene, polybutylene terephthalate and polyamide 6.
3. The antibacterial thermoplastic resin composite material according to claim 1, characterized in that: The preparation method of the thymol-titanium dioxide core-shell antibacterial agent comprises the following steps: (1) adding titanium dioxide, thymol and a cross-linking agent into an acetone aqueous solution, stirring and reacting to obtain a titanium dioxide-thymol mixed solution A; (2) The titanium dioxide-thymol mixed solution A is filtered to obtain a solid B, and the solid B is washed and vacuum dried in sequence, and then ground to obtain a core-shell antibacterial agent with thymol as a core and titanium dioxide as a shell.
4. The antibacterial thermoplastic resin composite material according to claim 3, characterized in that: The mass ratio of titanium dioxide, thymol and cross-linking agent is (30-40): (30-36): (0.2-0.4).
5. The antibacterial thermoplastic resin composite material according to claim 3, characterized in that: The cross-linking agent is tert-butyl peroxide, dicumyl peroxide or 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane.
6. The antibacterial thermoplastic resin composite material according to claim 3, characterized in that: The stirring reaction in step (1) refers to stirring the reaction at 40-60° C. for 8-12 hours; The vacuum drying temperature in step (2) is 50-70° C. and the drying time is 8-12 h; the product is ground through a 500-mesh sieve.
7. The antibacterial thermoplastic resin composite material according to claim 1, characterized in that: The antioxidant is one of tris(2,4-di-tert-butyl)phenyl phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene or a mixture of several thereof.
8. A method for preparing an antibacterial thermoplastic resin composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Weigh 80-100 parts of a thermoplastic resin, 2-4 parts of an antibacterial agent, and 0.1-0.5 parts of an antioxidant, mix and stir to obtain a mixture; (2) Extruding the mixed material obtained in step (1) from an extruder and granulating it to obtain a thermoplastic resin composite material.